Targeted therapy in melanoma - Tawbi, Hussein (Dove Medical Press, 2009)
Malignant melanoma is a highly lethal disease unless detected early. Single-agent chemotherapy is well tolerated but is associated with very low response rates. Combination chemotherapy and biochemotherapy may improve objective response rates but do not prolong survival and are associated with greater toxicity. Immunotherapeutic approaches such as highdose interleukin-2 are associated with durable responses in a small percentage of patients, but are impractical for many patients due to accessibility and toxicity issues. Elucidations of the molecular mechanisms of carcinogenesis in melanoma have expanded the horizon of opportunity to alter the natural history of the disease. Multiple signal transduction pathways seem to be aberrant and drugs that target them have been and continue to be in development. In this review we present data on the most promising targeted agents in development, including B-raf inhibitors and other signal transduction inhibitors, oligonucleotides, proteasome inhibitors, as well as inhibitors of angiogenesis. Most agents are in early phase trials although some have already reached phase III evaluation. As knowledge and experience with targeted therapy advance, new challenges appear to be arising particularly in terms of resistance and appropriate patient selection.